365 Days of Wonder : Mr. Browne's Book of Precepts - Palacio, R. J. (Alfred A. Knopf, an imprint of Random House Children's Books, 2014)
"A book of precepts, with one saying for each day, from Auggie's teacher Mr. Brown"--